A ambivalência do cômico no teatro de Machado de Assis - Araújo, Ana Paula Rocha Vital (2015)
Theatrical critic to the twenty years old, Machado de Assis recorded the transformations that brazilian theater was passing in the mid-nineteenth century. With the flourishing of the french realist theater, the romantic theatrical model, laden in the scenic exaggerations, as in the which respect the stage of ornamentation as the physical movements of the actors, it becomes criticized and fought. What is desired was a scenic and repertoire renovation from a greater restraint of artists and plots replacement whose central themes were the nation for thematic based on family problems. Documenting this moment of transition from brazilian theater and stimulated by new realistic comedies, Machado de Assis makes his first comic plays. Starting from the perspective that laughter is an indispensable function to thought, in that makes us see the word with another eyes, it has the relevant analysis of the functions and comic procedures in Machado de Assis plays. With this purpose, we selected two pieces: Hoje Avental, amanhã luva (1860) and O caminho da porta (1862), works whose central themes revolve around the female figure. As subsidies to support our analyzes, we base on the theories about the comic from Bergson (2007), Freud (1977) and Jolles (1976), from which we realize that the comic undertaken by Machado de Assis as can assume an act of social significance that fulfills the task of correcting deviated behavior, approaching thus the Bergson's theory as also takes the freudian perspective that the comic raises pleasure in that it provides the leakage of repressed contents, revealing, therefore, what is hidden.